2019
DOI: 10.1002/app.48573
|View full text |Cite
|
Sign up to set email alerts
|

Spray processable polyurea formulations: Effect of chain extender length on material properties of polyurea coatings

Abstract: The increasing usage of polyurea coatings has attracted the attention of researchers worldwide. Commercial polyurea formulations contain chain extenders as an essential ingredient, which increases the possibility of intermolecular H-bonding by bringing the urea linkages closer. In this work, we establish the effect of increasing chain length of chain extender on the material properties of the polymer. Different types of chain extender were blended with a long chain diamine and subsequently reacted with an MDI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Their studies further confirm that it is prudent to introduce a blend of aromatic and aliphatic chain extender. It appears that in the presence of a combination of these two, the growing macromolecule orients in a manner which results in optimal H-bonding [12,13]. It has also been found that the sub-zero glass transition temperature (T g ) shifts methodically towards higher temperature as the total hard segment content decreased.…”
Section: Selection Of Chain Extender: Effect Of Increasing Vicinity Of Urea Linkagesmentioning
confidence: 99%
“…Their studies further confirm that it is prudent to introduce a blend of aromatic and aliphatic chain extender. It appears that in the presence of a combination of these two, the growing macromolecule orients in a manner which results in optimal H-bonding [12,13]. It has also been found that the sub-zero glass transition temperature (T g ) shifts methodically towards higher temperature as the total hard segment content decreased.…”
Section: Selection Of Chain Extender: Effect Of Increasing Vicinity Of Urea Linkagesmentioning
confidence: 99%
“…Polyurea (PU) coatings are gaining attention because of its rapid cure, even at low temperatures, water resistivity, outstanding mechanical properties, and chemical durability. [1][2][3] The fast reaction makes PU especially suitable for outdoor applications. [4][5][6] Due to its specific curing profile and exceptional film properties, PU materials are used in roof coatings, flat roof repair, pipe protection, tank coatings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this compound can act as a monomer, a polymer, or a mixture thereof. In almost all commercial formulations, the resin is a homogenous blend of polyetheramine characterized by repeating oxypropylene units in the backbone and chain extender [ 1 , 2 ]. In polyurethanes, hydroxyl-terminated compounds are present instead of amines, while the cross-linking reaction occurs through isocyanate and both amine and hydroxyl-terminated compounds in hybrids [ 3 ].…”
Section: Introductionmentioning
confidence: 99%